Cross sections and analysing power energy-sharing distributions of valence (p,2p)-knockout from 208Pb with a projectile of 200MeV - Bezuidenhout, Jacques (Stellenbosch : Stellenbosch University, 2012)
Thesis (MSc)--Stellenbosch University, 2000.